2011
DOI: 10.1590/s0034-737x2011000500017
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de biorregulador na germinação e no vigor de sementes de soja

Abstract: Effect of plant growth regulator on germination and vigor of soybean seedsPlant growth regulators can enhance growth and development of plants and induce cell division. They can also interfere in seed germination. The objective of this study was to evaluate the physiological quality of seeds treated with a plant growth regulator. Seeds of nine soybean (Glycine max (L.) Merrill) commercial cultivars were treated with four concentrations (400; 500 and 600 mL 100 kg -1 seeds) of the plant growth regulator Stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 11 publications
3
21
0
16
Order By: Relevance
“…Considering the possible content of phytohormones (or similar) of the liquid extract, these results are consistent with the report of Moterle et al (2011) and Vieira and Castro (2001) who found that there were positive changes in the performance of seedlings, increase in the length of the aerial part of the soybean seedlings treated with Stimulate®. One was Bioregulator registered and recommended for soybean culture (EMBRAPA, 2014).…”
Section: Resultssupporting
confidence: 92%
“…Considering the possible content of phytohormones (or similar) of the liquid extract, these results are consistent with the report of Moterle et al (2011) and Vieira and Castro (2001) who found that there were positive changes in the performance of seedlings, increase in the length of the aerial part of the soybean seedlings treated with Stimulate®. One was Bioregulator registered and recommended for soybean culture (EMBRAPA, 2014).…”
Section: Resultssupporting
confidence: 92%
“…However, productivity increases are still necessary and possible, through practices such the use of high quality seeds (Mertz et al, 2009;Moterle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The attributes which determine the seeds quality are related to genetic, physical, physiological and sanitary factors. These attributes can be characterized by germination, vigor and longevity tests which show their viability (Moterle et al, 2011;Nerling et al, 2013).…”
Section: Introductionmentioning
confidence: 99%